207k views
5 votes
2/3w - 1/4 = 2/3(w - 1/4)

User Adobe
by
7.0k points

1 Answer

2 votes

Answer:

No solution

Step-by-step solution:

We are given an expression:


(2)/(3) w-(1)/(4) =(2)/(3) (w-(1)/(4) )

We have only one variable
w so we will make
w the subject and solve for it.


(2)/(3) w-(1)/(4) =(2)/(3) (w-(1)/(4) )

Solving the brackets first to get:


(2)/(3) w -(1)/(4) =(2)/(3) -(1)/(6)

Taking LCM on both sides to get:


(8w-3)/(12) =(4w-3)/(6)

By cross multiplication:


6(8w-3)=12(4w-3)


48w-18 = 48w -36


48w - 49w -18 + 36 = 0


w gets cancelled so we are left with
18\\eq 0

Therefore,
w has no solution.

User GMB
by
6.7k points